Desempenho de crianças do ensino fundamental na solução de problemas aritméticos - OLIVEIRA, Marinalva Silva (2011)
Performance of children of the elementary school in arithmetics problems solving This study compared the performance of students of the first year of the elementary school (groups 1F and 1IN) and students of the second year of elementary school (groups 2F and 2IN), tested at the beginning (IN) or at the end of the school year (F), in mathematical problems solving. Thirty eight participants divided into 4 groups were submitted to the same procedure, that consisted in mathematical problems oral presentation. After each answer the participants were asked about form of solution. Data was analysed related to the amount of correct answers and the strategies employed. Correct answers and the use of writing were more frequent in Group 2F and less frequent in Group 1IN. Groups 2F and 1F showed a more frequent use of algorithms. Results also show a better performance of Group 1F related to Group 2IN, suggesting that the history of recent frequency to school favours the performance of the participants.